Direct versus video laryngoscopy with standard blades for neonatal and infant tracheal intubation with supplemental oxygen: a multicentre, non-inferiority, randomised controlled trial. (February 2023) - Riva, Thomas; Engelhardt, Thomas; Basciani, Reto; Bonfiglio, Rachele; Cools, Evelien; Fuchs, Alexander; Garcia-Marcinkiewicz, Annery G; Greif, Robert; Habre, Walid; Huber, Markus; Petre, Maria-Alexandra; von Ungern-Sternberg, Britta S; et al.
Summary: Background: Tracheal intubation in neonates and infants is a potentially life-saving procedure. Video laryngoscopy has been found to improve first-attempt tracheal intubation success and reduce complications compared with direct laryngoscopy in children younger than 12 months. Supplemental periprocedural oxygen might increase the likelihood of successful first-attempt intubation because of an increase in safe apnoea time. We tested the hypothesis that direct laryngoscopy is not inferior to video laryngoscopy when using standard blades and supplemental oxygen is provided. Methods: We did a non-inferiority, international, multicentre, single-blinded, randomised controlled trial, in which we randomly assigned neonates and infants aged up to 52 weeks postmenstrual age scheduled for elective tracheal intubation to either direct laryngoscopy or video laryngoscopy (1:1 ratio, randomly assigned using a secure online service) at seven tertiary paediatric hospitals across Australia, Canada, Italy, Switzerland, and the USA. An expected difficult intubation was the main exclusion criteria. Parents and patients were masked to the assigned group of treatment. All infants received supplemental oxygen (1 L/Kg per min) during laryngoscopy until the correct tracheal tube position was confirmed. The primary outcome was the proportion of first-attempt tracheal intubation success, defined as appearance of end-tidal CO2 curve at the anaesthesia monitor, between the two groups in the modified intention-to-treat analysis. A 10% non-inferiority margin between direct laryngoscopy or video laryngoscopy was applied. The trial is registered with ClinicalTrials.gov (NCT04295902 ) and is now concluded. Findings: Of 599 patients assessed, 250 patients were included between Oct 26, 2020, and March 11, 2022. 244 patients were included in the final modified intention-to-treat analysis. The median postmenstrual age on the day of intubation was 44·0 weeks (IQR 41·0–48·0) in the direct laryngoscopy group and 46·0 weeks (42·0–49·0) in the video laryngoscopy group, 34 (28%) were female in the direct laryngoscopy group and 38 (31%) were female in the video laryngoscopy group. First-attempt tracheal intubation success rate with no desaturation was higher with video laryngoscopy (89·3% [95% CI 83·7 to 94·8]; n=108/121) compared with direct laryngoscopy (78·9% [71·6 to 86·1]; n=97/123), with an adjusted absolute risk difference of 9·5% (0·8 to 18·1; p=0·033). The incidence of adverse events between the two groups was similar (–2·5% [95% CI –9·6 to 4·6]; p=0·490). Post-anaesthesia complications occurred seven times in six patients with no difference between the groups. Interpretation: Video laryngoscopy with standard blades in combination with supplemental oxygen in neonates and infants might increase the success rate of first-attempt tracheal intubation, when compared with direct laryngoscopy with supplemental oxygen. The incidence of hypoxaemia increased with the number of attempts, but was similar between video laryngoscopy and direct laryngoscopy. Video laryngoscopy with oxygen should be considered as the technique of choice when neonates and infants are intubated. Funding: Swiss Pediatric Anaesthesia Society, Swiss Society for Anaesthesia and Perioperative Medicine, Foundation for Research in Anaesthesiology and Intensive Care Medicine, Channel 7 Telethon Trust, Stan Perron Charitable Foundation, National Health and Medical Research Council.